Training of Trainers (TOT) Peningkatan Pemahaman Perlindungan Konsumen Sektor Jasa Keuangan - Krisnaningsih, Erni; Basri, Alamsyah; Amilia, Euis; Ilmi, Yusina Fadla; Denardo, Denardo; Dwiyatno, Saleh (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2024)
Project of PKM in Training of Trainer (ToT) aims to encourage synergy between OJK financial services business actors and university academics to provide literacy and education on Understanding Consumer Protection in the Financial Services Sector to the community in Serang Regency. The pre-test results show the ability and understanding of ToT participants, there are participants who do not understand the Consumer Protection of the Financial Services Sector. Post-test results after the implementation of ToT training showed an increase in participants' understanding of the duties, functions and objectives of the financial services authority in consumer protection, in the financial services sector by 11.4% and related to the level of understanding of participants in recognizing illegal and legal investments there was an increase in understanding by 21.9%. In general, there was a significant increase in the understanding of the training participants after participating in the ToT activities. Furthermore, there is a need for further activities from PKM ToT with training activities to increase skills and understanding for the community to use the financial information service system (SLIK)..